BIMBINGAN dan KONSELING UNTUK PENDIDIKAN ANAK USIA DINI (PAUD) - AR Koesdyanrho, Lydia Ersta Kusumaningtyas & (Adi Widya : Jurnal Pengabdian Masyarakat, 2017)
The Title of This Devotion Counseling Guidance for Early Childhood Education. This devotion is done because the teacher education background in kindergarten Lakshmi 7 surakarta only vocational school that has never known what is guidance and counseling and also added with parents of student which relative high school education. So counseling and counselor training is very necessary to be implemented. This is because of the importance of counseling that should be implemented in Early Childhood Education (PAUD). The purpose of the devotion is to increase knowledge about the importance of bUD is the teacher and the parents of the students. Counseling and counselor training was held 6 meetings. Ie from April 15 to May 6, 2017 and held every weekend for 3 hours. For the first day of the counseling about the importance of guidance and counseling in early childhood as well as parents and teachers as PAUD counselors. Then carried out counselor training. Until finally the parents and teachers have the importance of counseling guidance for early childhood and how to become PAUD counselors. As a result parents and teachers can understand about the guidance of early childhood counseling and can become an early childhood counselor. So it can be concluded that this activity is very useful for teachers and parents of kindergarten Lakshmi 7. Given the background of parents' education is relatively low education or only high school graduates and teachers in kindergarten Lakshmi 7 is only the background of SMK as well. Keywords: Counseling Guidance,, Early Childhood Education